Nobody Wanted to play - Hunt Roderick; Alex Brychta
Wilf was upset that nobody wanted to play with him. He went to the park by himself and pretended to play different roles like a spaceman, juggler, cowboy, and more. Eventually more children joined Wilf in playing together at the park.
Keywords: English-Oxford Reading Tree